2009
DOI: 10.1016/j.bbagrm.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Interactome for auxiliary splicing factor U2AF65 suggests diverse roles

Abstract: U2 small nuclear ribonucleoprotein auxiliary factor (U2AF) is an essential component of the splicing machinery that is composed of two protein subunits, the 35 kD U2AF 35 (U2AF1) and the 65 kD U2AF 65 (U2AF2). U2AF interacts with various splicing factors within this machinery. Here we expand the list of mammalian splicing factors that are known to interact with U2AF 65 as well as the list of nuclear proteins not known to participate in splicing that interact with U2AF 65 . Using a yeast two-hybrid system, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…The U2 snRNP has SF3A1-A3 and SF3B1-B5. U2AF65 is a U2 snRNP auxiliary factor that is an essential component of the pre-mRNA splicing machinery (Prigge et al, 2009). regulators include KAT2B, HDAC1/2, SWI/SNF, CTCF, MeCP2, WDR5/MLL (an H3K4 methyltransferase), EZH2 (a repressor), and mediator , Sjolinder et al, 2005, Tyagi et al, 2009, Khan et al, 2012, Maxwell et al, 2013, Tsai et al, 2010, Gardini and Shiekhattar, 2015.…”
Section: H3k4me3 Readersmentioning
confidence: 99%
“…The U2 snRNP has SF3A1-A3 and SF3B1-B5. U2AF65 is a U2 snRNP auxiliary factor that is an essential component of the pre-mRNA splicing machinery (Prigge et al, 2009). regulators include KAT2B, HDAC1/2, SWI/SNF, CTCF, MeCP2, WDR5/MLL (an H3K4 methyltransferase), EZH2 (a repressor), and mediator , Sjolinder et al, 2005, Tyagi et al, 2009, Khan et al, 2012, Maxwell et al, 2013, Tsai et al, 2010, Gardini and Shiekhattar, 2015.…”
Section: H3k4me3 Readersmentioning
confidence: 99%
“…However, in the budding yeast Saccharomyces cerevisiae, the large subunit is dispensable and the small subunit is absent (1). In humans, U2AF65 interacts with several splicing factors (BBP/SF1, UAP56, SAP155 [or SF3b155], and p54) (1,14,19,43,45,70) and facilitates branch point recognition (2, 4). The mammalian U2AF65 is found to be dispensable for splicing of some introns in vitro in the presence of the SR protein SC35 (36).…”
mentioning
confidence: 99%
“…It is of note that both U2af2 and Erh have been implicated in the regulation of RNA splicing [60, 61]. Furthermore, U2af2 interacts with Rbm39 in yeast-two hybrid assays [62]. In the current study, Rbm39 was also identified as a DEPDC1B-interacting protein.…”
Section: Discussionmentioning
confidence: 49%